Quantifying and modelling the game speed outputs of English Championship soccer players. Issue 2 (4th March 2022) - Connor, Mark; Mernagh, Dylan; Beato, Marco
ABSTRACT: This study aims to quantify and model the game-speed demands of professional soccer players competing in the English Championship league, to compare the effect of match location and to examine the effect of playing position on game-speed outputs across the season. Twenty-eight male professional soccer players were enrolled. Moving average calculations were applied to the raw GNSS (STATSports) speed data of each player's duration matches (home = 14 and away = 9). Positional groups were centre-back (CB), full-back (FB), centre-midfield (CM), wing-midfield (WM) and centre-forward (CF). The maximum value across each of the moving average window durations was extracted and converted to units of metres per minute. Power-law models were fitted to all observations (R2 = 0.64), home only (R2 = 0.98), and away only (R2 = 0.98). No significant effects are observed in game-speed outputs when home and away games are analysed. Significant differences were seen between the following positional groups; CBvs.CF ( d = −0.323), CM ( d = −0.530) and FB ( d = −0.350). CM displayed positive difference compared to WM ( d = 0.614). This study reported power-law model fitted game speed. Players' positional groups have significantly different game-speed demands, which should be considered during match analysis and training periodization. This study found that game speed is not affected by the location of the match.